(untitled) (Journal of Da’wah, 2022)
Radio has become an influential communication media since it’s commencement . Eventhought, radio was once advertised as the fifth plantation after newspaper. By the development of technology, radio has growth by number of variations. There was a time when radio was as big as a televition station. This period is raised as the radios’ times. The growths of tecnology have developed the media, it was configurate the users, and then also configurate the society and its culture. Besides, radio as a communication mass media, hinge on audio or sound in transmission communication messages. The potential in radio are assists to conveyance of information, moreover the information received in various situations and conditions. This is a chance for students of the Islamic communication and broadcasting department, Faculty of Humanities Adab, and Da’wah, State Islamic University Sjech M. Djamil Djambek Bukittinggi in role of the sharing time program for the pro 2 Radio Republic of Indonesia (RRI) Bukittinggi. This paper uses a qualitative research method with a descriptive approach.